2016
DOI: 10.1093/ndt/gfv443
|View full text |Cite
|
Sign up to set email alerts
|

Primary seroresponses to double-dose compared with standard-dose hepatitis B vaccination in patients with chronic kidney disease: a systematic review and meta-analysis

Abstract: The current data do not support clinical guideline recommendations for administering double-dose vaccination for patients with CKD as seroconversion was not improved and seroprotection was inadequately assessed. Large high-quality studies are required to overcome the current evidence gap regarding vaccine dosing in CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
2
20
0
1
Order By: Relevance
“…Thereby, 30-70% of dialysis patients do not respond to their first hepatitis B vaccination [12,13] and 50-70% to a second vaccination, while the response rate in the general population is about 90% [14]. The antibody titre is also lower in dialysis patients with a per-centage of seroprotection of about 30% in a recent metaanalysis [15], and the duration of seroprotection is shorter. Hence, achieving proper and durable HBV vaccine response is still an unmet medical need in dialysis patients, and defining strategies to improve vaccine response is necessary.…”
Section: Discussionmentioning
confidence: 98%
“…Thereby, 30-70% of dialysis patients do not respond to their first hepatitis B vaccination [12,13] and 50-70% to a second vaccination, while the response rate in the general population is about 90% [14]. The antibody titre is also lower in dialysis patients with a per-centage of seroprotection of about 30% in a recent metaanalysis [15], and the duration of seroprotection is shorter. Hence, achieving proper and durable HBV vaccine response is still an unmet medical need in dialysis patients, and defining strategies to improve vaccine response is necessary.…”
Section: Discussionmentioning
confidence: 98%
“…37 However, a concern is that seroprotection rates in these SOT candidates are still suboptimal even with the double-dose (40 µg) hepatitis B immunization schedule. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] The expectation of low effectiveness of currently licensed HBV vaccines in renal transplant recipients was shown to be the most important barrier to guideline adherence among Dutch nephrologists. 38 Similarly for liver transplant candidates, HBV immunity rate was significantly lower in patients with more advanced liver dis- should be immunized with the hepatitis B vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…14,20,23,24 A recent systematic review also reported a poorer immune response in patients with end-stage renal disease with 24%-42% seroprotection after standard-dose (20 µg) HBV vaccination and 51%-69% after double-dose (40 µg) vaccination. 25 Low success rates of HBV vaccination have also been reported in cardiac and pulmonary transplant candidates. 26,27 Recent data on the immunization rate among SOT candidates in a low HBV endemic region and the effect of universal infant vaccination have not been explored thus far.…”
Section: Introductionmentioning
confidence: 99%
“…The vaccine schedule recommended for pre-dialysis patients consists of 3 shots with standard doses of hepatitis B virus vaccine (20 mcg; 0,1, and 6 months) (7). A recent systematic review concluded that double-dose vaccination for CKD patients did not improve seroconversion compared to patients on standard HBV vaccine; the lower number of studies could be implicated in these conflicting findings (41).…”
Section: Discussionmentioning
confidence: 99%